Aesthetic categories: construction and validation of the AESCATScale - Sobreira, Michelle do Carmo; Silva, Joelma Soares da; Lopes, Luma Louise Sousa; Mota, Márcio de Oliveira (Revista de Administração da UFSM, 2023)
Purpose: The aim of this study focused on the elaboration and validation of an organizational aesthetic perception scale (AESCATScale) to be used in understanding individuals’ perceptions of organizational life. Design/methodology/approach: We carried out a literature review, exploratory interviews, two separate surveys, and multivariate analyses. The scale was validated through an application with a large sample of college professors. Findings: Our outcomes consisted of a multidimensional construct model for the perception of organizational aesthetics (AESCATScale), with seven dimensions and 20 items. According to our analysis, the organizational aesthetics construct is consistent and may be the basis for future studies on the subject. Research limitations/implications: We highlight three peculiar limitations to the research: a) the subjective nature of the theme, b) the lack of comprehension of some categories by respondents and c) the sample used was chosen for its accessibility and to have been restricted to college professors of a single state in Brazil. Practical implications: The AESCATScale may reveal the sensitive logic underlying several organizational practices in the workplace based on a sensitive point of view. Also, it can be a valuable tool to aid in a manager’s decision-making in situations of change. Originality/value: This study introduces a differentiated approach to organizational management that can sometimes be missed due to its abstract nature. Therefore, it introduces a novelty research tool that can be used in corporate and academic environments.